Implementasi Sila Keempat Pancasila Sebagai Etika Partisipasi Politik Di Era Digital - Alifah, Radhya Putri Salwa; Purnama, Dona (Academy of Social Science and Global Citizenship Journal, 2025)
The development of information and communication technology has brought about major changes in the mindset and behavior of the younger generation, especially Generation Z. Social media, as an integral part of their lives, plays an important role in shaping their perceptions of various social and citizenship issues. This study aims to examine how social media influences Generation Z's understanding of their rights and obligations as citizens. The method used in this study is a literature study with a descriptive qualitative approach, which examines various journals, scientific articles, and other relevant sources. The results of the study show that social media has two sides to its influence: on the one hand, it can increase political awareness and social participation; on the other hand, social media can also give rise to misinformation that obscures understanding of civic responsibility. Therefore, adaptive digital literacy and civic education are needed to equip Generation Z with a critical and responsible understanding of their rights and obligations as citizens in the digital era.